A solid grounding: prescribing skills training. (June 2015) - Kirkham, Deborah; Darbyshire, Daniel; Gordon, Morris; Agius, Steven; Baker, Paul
Summary Background Prescribing is an error‐prone process for all doctors, from those who are newly qualified through to those at consultant level. Newly qualified doctors write the majority of in–patient prescriptions and therefore represent an opportunity for safety improvement. Attention to prescribing as a patient‐safety issue and potential educational interventions to help improve the situation have been published, but offer little to inform educators why and how any interventions may succeed. In order to identify areas of good practice, and to provide evidence of areas requiring further investigation and innovation, we aimed to ascertain the full range of prescribing practices for final‐year medical students and newly qualified doctors across a large geopolitical region of the UK. Methods A questionnaire methodology was used. One questionnaire was sent to those responsible for final‐year education, and a further, different questionnaire was sent to those responsible for the training of newly qualified doctors, asking about prescribing education in their locality. Questionnaires were sent to 15 hospitals in total. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Prescribing is an error‐prone process for all doctors </boxed-text> Results Twelve hospitals contributed to final‐year medical student data: a response rate of 80 per cent. A variety of methods, including student assistantship, pharmacist‐led skills sessions and practical assessment, were offered to varying degrees. Free‐text responses identified opportunities for different prescribing education and support. All 15 hospitals provided data on doctors' education, with interventions including e–learning, assessment and support from ward‐based pharmacists. Discussion Current education focuses on the technical and knowledge‐based paradigm of prescribing. Human factors and the impact of electronic prescribing should play a part in future developments in prescribing education.